Effect of certain indigenous medicinal plants on follicular development and steroidogenesis in rats - MEHROTRA, S; SHANKER, UMA; MAJUMDAR, A C; PALIWAL, O P; AGARWAL, S K (The Indian Journal of Animal Reproduction, 2023)
50% ethanolic plant extracts of Murraya koenigii (curry leaf plant) and Urtica dioica (Bichchu grass) were given P.O. indoses of I 00, 300 and I 000 mg.kg·' during di estrus to estrus in six groups (n=6) of I 2-1 S week aged female rats against a controlgroup, based on LD,0 studies. Rats were sacrificed during estrus, based on vaginal smear technique and dissected out to remove boththe ovaries. Total number of large surface follicles were counted and ovaries were processed for histological and histochemical studiesusing standard procedures, to determine embedced follicular population and expression of steroidogenic enzymes i.e. Glucose-6-phosphate dehydrogenase (G6 PD) and 3 ~-hydroxy-ti.5-steroid dehydrogenase (3~HSD), respectively. Results indicated significantlyhigher number of large surface and embeded follicles in Murraya 1000 mg kg·' treated group of rats with relatively higher expressionof G6PD and 3~HSD as compared to control and other groups.
Keywords: Medicinal plants; follicular development; steroidogenesis; rats